Multiplication of Polynoimals by Polynomials
Multiplying Binomial by a Trinomial
Ex 8.4, 1 (i)
Ex 8.4, 1 (ii)
Ex 8.4, 1 (iv)
Ex 8.4, 1 (iii) Important
Ex 8.4, 2 (i)
Ex 8.4, 2 (ii) Important
Example 8 (i)
Example 9 (i)
Ex 8.4, 2 (iii)
Ex 8.4, 2 (iv) Important
Ex 8.4, 1 (v) Important
Ex 8.4, 1 (vi) Important
Ex 8.4, 3 (iii) Important
Ex 8.4, 3 (i) You are here
Ex 8.4, 3 (ii)
Ex 8.4, 3 (vi)
Ex 8.4, 3 (viii)
Example 10
Ex 8.4, 3 (iv)
Ex 8.4, 3 (v) Important
Ex 8.4, 3 (vii) Important
Multiplication of Polynoimals by Polynomials
Last updated at April 16, 2024 by Teachoo
Ex 8.4, 3 Simplify. (i) (𝑥^2−5) (𝑥+5)+25Here, there are 2 expressions: 1st expression = (𝑥^2−5) (𝑥+5) 2nd expression = 25 Solving 1st expression (𝒙^𝟐−𝟓) (𝒙+𝟓) = 𝑥^2 (𝑥+5)−5(𝑥+5) = (𝑥^2 × 𝑥)+(𝑥^2 × 5)−(−5 × 𝑥)−(5 × 5) = 𝒙^𝟑+𝟓𝒙^𝟐−𝟓𝒙−𝟐𝟓 Now, our expression is (𝒙^𝟐−𝟓) (𝒙+𝟓)+𝟐𝟓 = 𝑥^3+5𝑥^2−5𝑥−25+25 = 𝒙^𝟑+𝟓𝒙^𝟐−𝟓𝒙